Changeover during in situ compositional modulation of hexacyanoferrate (Prussian Blue) material - Bueno, Paulo Roberto [UNESP]; Gimenez-Romero, David; Gabrielli, Claude; Garcia-Jareno, Jose Juan; Perrot, Hubert; Vicente, Francisco (Amer Chemical Soc, 2006)
This paper describes the importance of (H2O)(6) clusters in controlling the properties of hexacyanoferrate (Prussian Blue) materials. A careful in situ study of compositional changes by using electrogravimetric techniques (in ac and dc modes) in hexacyanoferrates containing K+ alkali metals reveals the existence of a changeover in the properties of these films in a narrow potential range. Control of the compositional variation of the changeover is dependent on the K+ stoichiometric number in the compound structure. However, a specific K+ occupation in the compound structure activates the occupation of the (H2O)(6) cluster by H3O+ and/or H+, causing the changeover in the properties of hexacyanoferrate film. Thus, the information thus obtained is very useful for understanding the mechanisms involved in the electrochemical reversible switch between ferrimagnetism/paramagnetism, semiconductor/metal and electroluminescence/nonelectroluminescence properties of molecular cyanide materials.